A State-of-the-Art Review on the Security of Mainstream IoT Wireless PAN Protocol Stacks - Georgios Kambourakis (Symmetry, 2020)
Protocol stacks specifically designed for the Internet of Things (IoT) have become commonplace. At the same time, security and privacy concerns regarding IoT technologies are also attracting significant attention given the risks that are inherently associated with the respective devices and their numerous applications, ranging from healthcare, smart homes, and cities, to intelligent transportation systems and industrial automation. Considering the still heterogeneous nature of the majority of IoT protocols, a major concern is to find common references for investigating and analyzing their security and privacy threats. To this end, and on top of the current literature, this work provides a comprehensive, vis-à-vis comparison of the security aspects of the thus far most widespread IoT Wireless Personal Area Network (WPAN) protocols, namely BLE, Z-Wave, ZigBee, Thread, and EnOcean. A succinct but exhaustive review of the relevant literature from 2013 up to now is offered as a side contribution.